Information, Kommunikation und Selbstdarstellung in mittelalterlichen Gemeinden - Haverkamp, Alfred (Schriften des Historischen Kollegs, 1998)
The accurate evaluation of the comparative advantages of investments is a core mission of corporate planning. This textbook presents the nature and objectives of investment theory, including aspects of perfect and imperfect capital markets under conditions of certainty, as well as investment theory involving uncertainty.